(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
The present essay through a close investigation of Salman Rushdie’s The Ground Beneath Her Feet (1999) and Fury (2002) looks into the challenges posed by global capitalism at the turn of the 21st century. The resilience of civilizations, in particular their cultural vocabulary and ethnic compositions, is explored in the face of the homogenizing drive of capitalist enterprise. The encounters between various ethnicities and cultures create liminal spaces of exchange where social innovation plays a critical role in shaping cross-cultural dialogues. Exchange takes place in terms of cultural values. Using the cultural dialectics of desire as a navigational compass the essay seeks to understand civilization(s) as a set of complex encounters. The multiplicity of civilizing processes at play on the global plane are scanned through the critical lens of “desire”, which is given a psycho-social orientation. The endless possibilities of neural networking opened up by globalization is born out of a legacy of conflict and interdependence. Two contrary trends emerge simultaneously; on the one hand there is an increasing tendency towards economic monopolization and Americanization and on the other hand there are decentralized and despatialized flows conducive to the growth of a hybrid cultural economy. Globalization at the turn of the century thus emerges as an economic and a cultural enterprise embracing plurality. The essay through the trope of desire explores the plural dynamics of globalization in the interaction, interdependence and contact between civilizations and cultures. It seeks to retrieve desire from the domain of market logistics and activate its ontological potential in terms of subjective empowerment and a critical aesthetics of change.